2006
DOI: 10.1177/1350508406061673
|View full text |Cite
|
Sign up to set email alerts
|

Academic Shape Shifting: Gender, Management and Identities in Sweden and England

Abstract: This article considers gender and managerial identities in organizational life, taking the recent change in higher education in Sweden and England with the coming of the new public management as the context in which to explore these issues. In reviewing the literature on gender identity and organization/management, which has moved from a pre-occupation with difference to an examination of the complex inter-relationship between gender and organization, an attempt is made to operationalize the concept of positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 24 publications
2
68
0
5
Order By: Relevance
“…It is hard to believe this would be the way to attract the most talented students and researchers (cf. Barry et al 2006).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It is hard to believe this would be the way to attract the most talented students and researchers (cf. Barry et al 2006).…”
Section: Discussionmentioning
confidence: 95%
“…It has been shown that some senior academics have been able to benefit from the increase of external funding and from networking with non-academic partners and that they identify themselves as research managers or academic entrepreneurs (Etzkowitz 1998(Etzkowitz , 2003Slaughter and Leslie 1997). Others-allegedly more often women than men (Barry et al 2006)-struggle with the increased workload and pressures related to accountability, performance measurement and external evaluation. The result is often confusion or a crisis of identity rather than the emergence of a well-defined new identity (e.g.…”
Section: Academic Identities In Changementioning
confidence: 99%
“…Individual identities and career discourse in the retail sector (Coupland, 2004) Coherence to the extent that individuals use dominant career discourse to construct identity; fragmentation in how different subject positions are constructed from this discourse Different subject positions alternately normalize and subvert dominant career discourses How the subject positions that emerged in the interviews were coconstructed as the researcher positions subjects in discourse and prompts them to give an account of themselves Professional identity of project managers (Hodgson, 2005) Coherence in how dominant discourse is used for identity work, particularly front stage; fragmentation how this is performed backstage Project managers perform identity work that conforms to but also subverts dominant discourses of professionalism How subject positions may be performed for researchers (backstage as opposed to front stage) Identity of consultants who sell advise on flexible work arrangements (Whittle, 2005) Coherence in how consultants reproduce dominant organizational discourses; fragmentation as they also dis-identify with these discourses Dis-identification reduces pressure for identity conformity while allowing individuals to perform in ways that conform How interpretations were co-constructed from the author's understandings of the participants' meanings as well as academic concepts Occupational identity of airline pilots (Ashcraft, 2005) Coherence in dominant discourses as to how occupational identity is becoming feminized; fragmentation of how subject positions are constructed in response to this Identity is a struggle over contested meanings as agents reiterate and alternately subvert dominant discourses of gendered work identities How researchers may impose meaning on the identity work of research subjects Identity of academics relative to discourses of new public management (Barry et al, 2006) Coherence of gendered identity; fragmentation of occupational identity; female identity work more fluid, male identity more stable.…”
Section: Reflection On Research Processmentioning
confidence: 99%
“…Indeed, how individual identity is constructed in organizations as the site of more or less managerial control is one of the most important and widely researched topics in organizational studies today (e.g. Ashcraft, 2005;Barry et al, 2006;Bergstroem and Knights, 2005;Down and Reveley, 2004;Hodgson, 2005;Merilainen et al, 2004). There are conference tracks and themed journal issues (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…La literatura en torno al tema define este tipo de masculinidad managerial, en primer lugar, a través de prácticas discursivas que se articulan con el capitalismo neoliberal, tales como la búsqueda de "posiciones de poder", la centralidad de la lógica de los "negocios" y el énfasis en la "productividad" (Martínez Alemán, 2014; Carvalho y Machado, 2010), las relaciones sociales de "competencia" (Martínez Alemán, 2014;Thomas y Davies, 2002;Carvalho y Machado, 2010;Prichard, 1996;Morley, 1999;Kerfoot y Knights, 1999), el "individualismo" (Martínez Alemán, 2014; Carvalho y Machado, 2010; Morley 1999), la "autonomía" (Connell y Messerschmidt, 2005, citados en Martínez Alemán, 2014) y la "independencia" (Thomas y Davies, 2002); todos estos rasgos van performando un "trabajador ideal", que se dedica por sí mismo a la productividad académica (Drago, 2007, citado en Martínez Alemán, 2014. En segundo lugar, están aquellos discursos ligados al método científico o al positivismo, tales como la "objetividad", la "racionalidad", y la "instrumentalidad" (Connell y Messerschmidt, 2005, citados en Martínez Alemán, 2014; Thomas y Davies, 2002;Carvalho y Machado, 2010;Barry, Berg y Chandler, 2006). Finalmente, están aquellas prácticas académicas de "homosociabilidad" que reproducen las exclusiones y fronteras de la participación a todo aquello que no coincide con tal masculinidad (Martínez Alemán, 2014;Prichard, 1996, citado en Collinson y Hearn, 1996.…”
unclassified